Pembagian Kerja Internasional yang Baru Sebagai Faktor Pengembangkan Wilayah - Siti S. Nurzaman (Journal of Regional and City Planning, 2006)
New International Division of Labor theory, introduced by Frobel, Heinrichs and Kreye in 1980, proposed that there is a qualitative shift in the nature of North-South relation in political economy. South is no longer a mere provider of raw material for North industries. Some parts of industrial processes, particularly those labor-oriented and use simple technologies, are relocated to South. It makes South becomes industrialized, although only caused by its cheap labor cost. Regions with abundant supply of cheap and docile labor, good harbor and other infrastructures become the favored location of these industries. As it usually coincides with national metropolis, increased regional inequalities are unavoidable. Due to telecommunication and Internet development, again, there is a qualitative shift in North-South economic relation. Practically all jobs that can be transmitted via Internet or telephone can be done in South who has lower salaries for the same quality work in North. It brings considerable local or regional economic development in some particular South countries.Keywords: New International Division of Labor, North-South, regional inequalities.